Means of criminalistic tactics: concept and system - Shevchuk, Viktor (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article is devoted to the study of current problems of criminalistic tactics, their concept and system. The modern tendencies and scientific approaches in criminalistics devoted to research of means of criminalistic tactics are analyzed. The modern understanding of the concept of means of criminalistic tactics is considered, its definition taking into account traditional and innovative approaches in criminalistic science is offered. It is noted that the concept of "means of criminalistic tactics", which is used today in criminalistics, is collective and generalizing, reflecting the complexity and versatility of the development and use of means to achieve the objectives of investigation and trial. The main innovative directions of research and problems of use of means of criminalistic tactics in law enforcement activity which provide its efficiency and effectiveness are defined. The interrelation of means of criminalistic tactics with practice, modern achievements of science and technology, tendencies of development of criminalistics and other sciences is traced, their innovative character is noted. It`s substantiated that one of the most important tasks of further development of criminalistics is to improve the existing system of criminalistic tactics in view of the emergence, development and current state of some innovative areas of criminalistics and expand the application of criminalistic tactics in various legal practices (investigative, judicial, prosecutorial, lawyer, search, detective, etc.). Research of new means of criminalistic tactics largely determines the innovative directions of modern criminalistic research in this field of knowledge. The use of criminalistic tactics should cover all types of activities, taking into account the trend of integration of scientific knowledge, application and implementation of interdisciplinary research and their further active use in legal practice. It is noted that further development requires the study of traditional and new means of criminalistic tactics such as: tactical admission; tactical recommendation; tactical combination; tactics of investigative (search) action; tactics of unspoken investigative (search) action; tactics of judicial action; tactics of organizing and conducting tactical operations, etc. Means of criminalistic tactics that are actually real used and potentially designed to achieve the objectives of criminal justice form a “tactical arsenal” of investigator, detective, prosecutor, operatives, lawyer, judge (court), which allows them to successfully solve tactical problems that arise at each stage criminal proceedings, taking into account the peculiarities of the event being investigated or considered in court, investigative and judicial situations, determinant factors influencing the choice and expediency of the use of certain types of tactical means or their system, etc. The system and main functions of criminalistic tactics, scientific approaches and proposals for solving the researched problems are formulated, innovative directions of development are determined.